50 Days Of War On Innocent Civilian: Ma'an News Agency Coverage Of Israeli And Palestinian Conflict - Wesam Almahallawi; Hasmah Zanuddin (Science Publishing Corporation, 2024)
Journal of Engineering & Technology, 7 (4.9) (2018) 145-150